Introduction: Firm level analysis with administrative data - Arndt, Channing; Davies, Rob; Gavin, Elizabeth; Mcmillan, Landon (Wiley, 2018)
This special issue focuses on a collaborative effort between the National Treasury and the South African Revenue Service (SARS) to employ administrative record data from SARS for economic policy analysis. It contains six research articles plus a synthesis article designed to draw out potential policy implications and to place this research into a broader context. Exploitation of tax administrative record data has become global best practice. We conclude that this effort demonstrates strong prospects for developing a better understanding of the South African economy with positive implications for economic policy formulation.